2016
DOI: 10.5812/traumamon.30277
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Hospital Management and Surge Capacity in Disasters

Abstract: BackgroundHospital administrators play a key role in the effective management of surge capacity in disasters, but there is little information available about the characteristics required to manage this.ObjectivesIn this study, we aimed to identify characteristics of hospital administrators that are important in the effective management of surge capacity in disasters.Materials and MethodsThis was a qualitative study. Semi-structured purposive interviews were conducted with 28 hospital administrators who had exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 25 publications
1
8
0
2
Order By: Relevance
“…Salmon et al (6) (2011) investigated the level of multi-agency coordination and its influencing factors in disasters. Furthermore, two studies showed that some factors lead to lack of coordination in disasters and emergencies; namely, lack of coordination failure in updating the rules, regulations, and guidelines in disaster management, and failure in assigning a commander in charge at the disaster management scene (7,8). In study, results revealed that the institutional framework should be strengthened through the initiation of the relevant strategies, training, and allocation of resources (9).…”
Section: Discussionmentioning
confidence: 99%
“…Salmon et al (6) (2011) investigated the level of multi-agency coordination and its influencing factors in disasters. Furthermore, two studies showed that some factors lead to lack of coordination in disasters and emergencies; namely, lack of coordination failure in updating the rules, regulations, and guidelines in disaster management, and failure in assigning a commander in charge at the disaster management scene (7,8). In study, results revealed that the institutional framework should be strengthened through the initiation of the relevant strategies, training, and allocation of resources (9).…”
Section: Discussionmentioning
confidence: 99%
“…Di antara 10 jurnal yang direview, terdapat 5 jurnal yang memiliki desain cross sectional (Alzahrani & Kyratsis, 2017), (Berhanu, Abrha, Ejigu, & Woldemichael, 2016), (Labrague et al, 2016), (Tzeng et al, 2016), dan (Seyedin et al, 2015) , 4 jurnal yang menggunakan penelitian kualitatif (Rabiei, Nakhaee, & Pourhosseini, 2014), (Yu et al, 2013), (Moghaddam, Saeed, Khanjani, & Arab, 2014) dan (Shabanikiya, Gorgi, Seyedin, & Jafari, 2016) dan 1 jurnal yang menggunakan Studi deskriptif (Yan et al, 2015). Dari 10 jurnal yang direview, terdapat 9 jurnal menggunakan program pendidikan dan pelatihan manajemen bencana (Alzahrani & Kyratsis, 2017); (Berhanu et al, 2016); (Rabiei et al, 2014); (Yu et al, 2013); (Moghaddam et al, 2014); (Labrague et al, 2016); (Tzeng et al, 2016); (Yan et al, 2015); dan (Seyedin et al, 2015) Pernyataan peneliti dari penelitian tersebut didukung oleh teori Happell (2009) yang menyatakan bahwa perawat berada dalam posisi untuk membantu mengatasi kesehatan jiwa pada saat krisis atau bencana, maka diperlukan dukungan psikologis berupa pengetahuan, yang mana pengetahuan tersebut terkait dengan teknik intervensi krisis dan bencana yang merupakan suatu keterampilan klinis yang penting bagi semua perawat, di luar dari tatanan klinis atau praktik spesialis (Happell et al, 2009dalam Stuart, 2016.…”
Section: Metodeunclassified
“…Sementara 5 jurnal (Rabiei et al, 2014), (Yu et al, 2013), (Berhanu et al, 2016), (Yan et al, 2015), dan (Moghaddam et al, 2014) yang menyimpulkan bahwa perawat perlu mempersiapkan diri pada aspek psikologis berupa kognitif, intelektual, minat, sikap, pendidikan keterampilan klinis dan pemahaman penyelamatan dengan prinsip-prinsip dasar dukungan psikososial. Sementara 1 jurnal (Shabanikiya et al, 2016) Seyedin, H et al, 2015;Luo, Y et al, 2013). Ketika merawat pasien, perawat dituntut untuk secara seimbang memenuhi kebutuhan fisik dan emosional dirinya maupun pasien dan keluarganya.…”
Section: Authorsunclassified
“…Most of the participants stated that there are a few exercises specific for hospital surge capacity in disasters: most 4 Trauma Mon. 2017; 22 (5):e59238.…”
Section: Theme 10: Weakness In Trainings On Hospital Surge Capacitymentioning
confidence: 99%
“…They are forced to increase their capacity in order to respond effectively to disasters and handle large numbers of victims (1)(2)(3)(4). The first step in policy-making and planning for hospital surge capacity at the national level is to understand the present condition, and its challenges (5).…”
Section: Introductionmentioning
confidence: 99%